Pelvic Organ Prolapse and its Associated Factors Among Women: A Facility Based Cross-sectional Study - Adamu Merga Msc; Kebebe Bidira Msc; Abdi Geda MPH; Desalegn Nigatu Msc; Ebissa Bayana Msc (SAGE Publishing, 2023)
Pelvic organ prolapse is the downward descent of female organs, including the bladder, small bowel, and large bowel, resulting in the protrusion of the vagina, uterus, or both. This disorder, exclusive to women, causes psychological trauma and social withdrawal, leading to an increased rate of gynecologic surgery. To assess the Pelvic Organ Prolapse and its associated factors among Women Visiting public Hospitals in south west Ethiopia. An institution-based cross-sectional study was conducted among gynecologic patients. A total sample size of 408 was allocated to the institutions proportional to their previous month's case load. Data were collected using an interviewer-administered structured questionnaire. The collected data were coded and entered into EpiData version 3.1, then exported to SPSS version 20 for descriptive and inferential analysis. Adjusted odds ratios (AOR) along with a 95% confidence level were estimated, and a P -value < .05 was considered statistically significant. Out of the intended sample size, 393 women participated in the study, resulting in a response rate of 96.3%. The overall magnitude of pelvic organ prolapse among the study participants was 19.8% (95% CI: 16.0, 24.1). Factors significantly associated with pelvic organ prolapse were place of residence (AOR = 2.21, 95% CI: 1.11, 4.40), parity (AOR = 2.82, 95% CI: 1.39, 5.72), age at first pregnancy (AOR = 2.32, 95% CI: 1.27, 4.26), and place of delivery of the first child (AOR = 4.18, 95% CI: 1.97, 8.85). The prevalence of pelvic organ prolapse is high. Place of residence, parity, age at first pregnancy, and place of delivery of the first child were factors significantly associated with pelvic organ prolapse. Therefore, different stakeholders, programmers, and implementers should take aggressive steps to prevent early pregnancy, train health professionals to encourage women to use family planning, and promote institutional delivery.